Evaluate the Suitability of Bush Bean with the Application of Nitrogenous Fertilizer - Paul, Alok Kumar; Sultana, Saima; Zahan, Mst. Musharrat; Bala, Tarun Kumar (International Journal of Bio-resource and Stress Management, 2017)
An experiment was conducted at Sher-e-Bangla Agricultural University farm, Dhaka during November, 2011 to March, 2012 to evaluate the suitability of BARI bush bean-1 with the application of nitrogenous fertilizer. The experiment was laid out following Randomized Complete Block Design (RCBD) with three replications. The source of the nitrogenous fertilizer was urea and organic manure cowdung. There are nine treatments i.e., 90 kg N supplied from urea; 80 kg N from urea+10 kg N supplemented by cowdung; 70 kg N from urea+20 kg N supplemented by cowdung; 60 kg N from urea+30 kg N supplemented by cowdung; 50 kg N from urea+40 kg N supplemented by cowdung; 40 kg N from urea+50 kg N supplemented by cowdung; 30 kg N from urea+60 kg N supplemented by cowdung; 90 kg N supplied from cowdung and control. BARI bush bean-1 variety was used as test crop. The result revealed that application of nitrogenous fertilizer from different sources found to be positive and significant on the growth and yield of bush bean. The highest plant height (43.67 cm), maximum number of plants m-2 (27.33), maximum number of seeds pod-1 (6.50), maximum number of branches plant-1 (7.66), maximum number of flowers plant-1 (27.67), highest pods plant-1 (25.0), longest pods length (12.89 cm) and the highest pod (13.44 t ha-1) yield was recorded from 50 kg N from urea+40 kg N supplemented by cowdung. In all case, lowest result was obtained from control treatment with no fertilizer.